Pruriception and neuronal coding in nociceptor subtypes in human and nonhuman primates - Klein, Amanda H.; Solinski, Hans Jürgen; Malewicz, Nathalie M; Ieong, Hada Fong-ha; Sypek, Elizabeth I; Shimada, Steven G; Hartke, Timothy V; Wooten, Matthew; Wu, Gang; Dong, Xinzhong; Hoon, Mark A; LaMotte, Robert H; et al. (eLife, 2021)
In humans, intradermal administration of β-alanine (ALA) and bovine adrenal medulla peptide 8-22 (BAM8-22) evokes the sensation of itch. Currently, it is unknown which human dorsal root ganglion (DRG) neurons express the receptors of these pruritogens, MRGPRD and MRGPRX1, respectively, and which cutaneous afferents these pruritogens activate in primate. In situ hybridization studies revealed that MRGPRD and MRGPRX1 are co-expressed in a subpopulation of TRPV1+ human DRG neurons. In electrophysiological recordings in nonhuman primates (Macaca nemestrina), subtypes of polymodal C-fiber nociceptors are preferentially activated by ALA and BAM8-22, with significant overlap. When pruritogens ALA, BAM8-22, and histamine, which activate different subclasses of C-fiber afferents, are administered in combination, human volunteers report itch and nociceptive sensations similar to those induced by a single pruritogen. Our results provide evidence for differences in pruriceptive processing between primates and rodents, and do not support the spatial contrast theory of coding of itch and pain.